Circular bioeconomy business models - recovering food products to reduce agricultural waste: cases from Burkina Faso, India, Kenya and Vietnam - Taron, Avinandan; Gebrezgabher, Solomie A.; Sanfo, S.; Ouédraogo, R.; Salack, S.; Diarra, K.; Ouédraogo, S.; Ojungobi, K.; Muthuswamy, S.; Malviya, T.; Odero, J.; Liem, D.D.; et al. (CGIAR Initiative on Nature-Positive Solutions, 2022)
Agricultural waste represents untapped resources that can be used to produce large value added products with many potential industrial applications. On-farm food waste comprises of harvest and post-harvest waste amounting to 1.2 billion tons per annum and measures up to USD 370 million. Production of food products and other outputs (like biofuel and compost) help in reduction of on-farm food waste and provide livelihood opportunities for the rural households. This reports highlights some innovative approaches across four countries which lead to reduction to food waste. The report cover 6 cases located in Burkina Faso, India, Kenya and Vietnam. The two business models identified in Ouagadougou are – (i) Waka group, that repurpose mango residues in to sweet and bio-vinyl vinegar called MISSIM vinegar, and (ii) SOFAB-SA utilizes oilseeds (such as peanuts, cotton, and soybeans) with blue cheese bran or corn, salt, or any other micro-ingredient to produce feed for livestock. From India, two such case studies are included – (i) Sai Shubhada agro industries is located in Ahmednagar, (Maharashtra, India), and converts bagasse, [a pulpy and fibrous residue of the sugarcane processing] into organic jiggery, and (ii) Arogyasangini Oil Mill, Mill has embarked on the mission to reintroduce oil extracted from the safflower seeds. Nadanya Greens located in Mbale, (Vihiga, Kenya) is exploring the use of farm waste from livestock to produce feeds for fish reared through three fish ponds. Xuan Tien Agricultural Cooperative, located at Yen Chau (Son La province, Vietnam), converts mango which is otherwise wasted post-harvest.